Strategies to improve engagement of long-lived elderly women (80+) in the interaction co-design process: challenges and lessons learned - Rosa, Valéria Argôlo; Matos, Ecivaldo de Souza (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2020: Anais do XIX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2020)
The growing population ageing highlights the need for strategies that enable older people to remain healthy and active. Digital technologies can contribute to this; however, the interaction of the elderly subject with these technologies is still frustrating, as these technologies are usually not designed with the needs and expectations of the elderly subject in mind. Engaging the elderly person in a process of interaction codesign may be a viable solution. However, conducting them in participatory activities is challenging. In this paper, we discuss our experiences in engaging ten elderly women, mostly long-lived (80+) in a process of interaction codesign, presenting some strategies used to improve engagement throughout the process, reflecting on the challenges and lessons learned. It is hoped that these strategies can help researchers and designers to engage elderly people in design processes with an effective participatory approach.